Analisis Bibliometrik : Tren Penelitian Kinerja Keuangan pada Usaha Mikro, Kecil dan Menengah (UMKM) - Ervina Ervina; Siti Mujanah; Achmad Yanu Alif Fianto (Transformasi Manageria: Journal of Islamic Education Management, 2024)
Several scientific publications related to Financial Performance have been carried out, in the Financial Performance of MSMEs there are several factors that have the potential to influence the financial health of an MSME to achieve long-term sustainability and success . This article aims to provide information regarding research trends that have been published regarding financial performance in the period 2019-2024. The method used in this research is to identify the number of journals using Harzing's Publish or Perish software, as well as bibliometric analysis using VOSviewer. The research results show that there are 200 publications with 26178 citations and 5235.60 citations/year that discuss Financial Performance. There are five main clusters based on the results of bibliometric analysis. This article also provides information related to research topics that have not been widely conducted so that it can provide benefits to stakeholders who may need it for further research.